Dynamical properties of the Molniya satellite constellation: Long-term evolution of orbital eccentricity. (February 2021) - Alessi, Elisa Maria; Buzzoni, Alberto; Daquin, Jérôme; Carbognani, Albino; Tommei, Giacomo
Abstract: The aim of this work is to analyze the orbital evolution of the mean eccentricity given by the Two-Line Elements (TLE) set of the Molniya satellites constellation. The approach is bottom-up, aiming at a synergy between the observed dynamics and the mathematical modeling. Being the focus the long-term evolution of the eccentricity, the dynamical model adopted is a doubly-averaged formulation of the third-body perturbation due to Sun and Moon, coupled with the oblateness effect on the orientation of the satellite. The numerical evolution of the eccentricity, obtained by a two-degree-of-freedom time dependent model assuming different orders in the series expansion of the third-body effect, is compared against the mean evolution given by the TLE. The results show that, despite being highly elliptical orbits, the second order expansion catches extremely well the behavior. Also, the lunisolar effect turns out to be non-negligible for the behavior of the longitude of the ascending node and the argument of pericenter. Finally, a frequency series analysis is proposed to show the main contributions that can be detected from the observational data. Highlights: The mean evolution of the orbital eccentricity of the Molniya satellites is analyzed. Different approximations of the lunisolar perturbations are studied. The role of the lunisolar perturbation on spacecraft orientation is remarked. In the given timeframe the chaotic nature of the problem does not affect the dynamics. The dominant periodic terms for the eccentricity are computed via Lomb–Scargle.